THE IMPACT OF VIOLENCE ON THE MENA REGION BUSINESS AND TRADE - Kairouz, Akl; Atala, Issam (European Scientific Journal, ESJ, 2014)
International business, historically, consisted of trade and transactions of goods being exchanged between different parties. It embodies manufacturing, purchasing, shipping and marketing of specific products under different brands and shapes within a highly competitive environment. After the research and findings conducted by Adam Smith and elaborated in his book the wealth of nations, the world made tremendous changes. The Division of work and tasks along with the evolution of the business concept and trade more control and coordination are needed nowadays. Since the evolution by itself created new processes to implement, the human behavior faced new challenges as well, the repercussion of the latter affected the exchange of goods and services system and the situation is becoming more ambiguous to understand if what drives the forces in trade are result of violence carried out by market forces or initiated in organizational culture! The success in international business depends on many key factors namely; the product’s quality and costs, the financial, political and legal ingredients, cultural differences and similarities, the availability of natural and human resources to acquire and sustain competitive advantage, within a secured and stable environment. This research focuses upon the cultural- military environment and its impact on national and international business trends in mainly the MENA region.